HUBUNGAN POSTUR KERJA DENGAN TINGKAT KELELAHAN OTOT PUNGGUNG PADA PEKERJA MEKANIK BENGKEL X SEMARANG - Rohkaeni, Sikis; Widjasena, Baju; Suroto, Suroto (Fakultas Kesehatan Masyarakat, 2018)
In the motorcycle maintenance activities use awkward posture, in a long time and repeatedly. Awkward posture can result in muscle fatigue or musculoskeletal disorder disorder (MSDSs). The purpose of this study was to analyze the corelation of work posture to the level of back muscle fatigue. The type of research used is quantitative with analytic observational research design and cross sectional research design. The population of the study were all mechanical workers of Bengkel X Semarang which amounted to 23 people with sampling method total sampling. The research instrument used is questionnaire, back dynaamometer and activity photo. The results showed there were 78.3% of respondents experiencing fatigue back muscles. Statistical analysis using Fisher Exact Test showed that there is a correlation between work posture with back muscle fatigue on the activity of checking/adjusting and lubricating gas cable (p = 0,033). There was no correlation between work posture with back muscle fatigue on air filtering activity (p = 1.00), oil check/change activity (p = 0,272), and brake checking activity (p = 0,539). It is recommended for workers to stretch on the sidelines of work. for the workshop manager to design/repair hydraulic aids so that it can be used by workers.